69.7k views
2 votes
PLEASE HELP!!!! ASAP!!!!

15 POINTS!!!!

Which expression is equivalent to (a6b−3)13 ?
a2b
ab
1ab
a3b

User Icehorn
by
5.4k points

2 Answers

2 votes

Answer:

13(a6b-3)

13×6 =a78b

13×3 = 39

and then you divide them

ab=78/39

Answer = a2b

User Abbe
by
5.2k points
4 votes

Answer:


\mathbf{a2b}

Explanation:

We can simplify it twice.

1) Simplify at first by the factor outside the parentheses, namely 13. So dividing by 13.


(a6b-3)13\\\\((a6b-3)13)/(13) \Rightarrow (a6b-3)

2) Since 6 and -3 are have as their GCD the number 3 then we can divide them both by 3.


((a6b))/(3)-(3)/(3)\Rightarrow (a2b)-1\Rightarrow\:a2b-1\Rightarrow a2b=1

3) As the question just asks us the left side of the equation before the equal sign. We can rewrite a2b -1 as a2b=1 then the answer


\mathbf{a2b}

User Prince Ahmed
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.